TEACHERS’ ATTITUDES TOWARDS CODE-SWITCHING IN ETHIOPIAN EFL CLASSROOMS - Tamene, Eyasu Hailu; Desalegn, Arega Temesgen (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
Code-switching or the use of L1 in teaching English is a pervasive and inevitable phenomenon in Ethiopia where teachers and students who own the same first language. Nevertheless, researches carried out on the teachers’ attitudes to pedagogical code-switching in Ethiopian context are scarce. This study, therefore, was designed to explore the attitudes of EFL teachers towards code-switching and seek their views on why code-switching should be used in English classrooms. This study employed a qualitative case study design where data were gathered through semi-structured interviews with five English teachers who were purposely selected from two secondary schools. The results revealed that the four teachers supported code-switching whereas one of the teachers had a different stance. All five teachers believed that code-switching should be used in a limited, selective, and purposeful way only when necessary. Furthermore, the results generally indicated that teachers had positive attitudes towards code-switching regarding academic, classroom management and socializing purposes although they had different stands on the specific functions of code-switching. Based on the results, it is possible to suggest that as code-switching is part and parcel of classroom discourse, teacher training programs should incorporate it as an effective instructional strategy.